Analysis of 110kV cable terminal abnormal partial discharge. Issue 1 (December 2020) - Duan, Xiaoli; Liu, Sanwei; Duan, Jianjia; Zeng, Zeyu; Liu, Yungen
Abstract: Through the introduction of a partial discharge fault event at the end of 110kV cable, through on-site inspection and on-site acoustic-electrical test, it is determined that the partial discharge at the end of 110kV cable is abnormal, and there are defects of suspension discharge or insulation discharge; Based on the phase analysis of high-frequency current signal and UHF time series data, the fault location analysis is carried out. The analysis shows that the cable A and B have the same insulation discharge defects. According to the reason of the defect, it is suggested to carry out the overhaul of the air chamber of the interval cable immediately to prevent the cable accident caused by the defective operation. It also proposes to standardize the cable terminal installation process and strengthen the cable quality supervision, focusing on and checking the equipment of the same manufacturer and model to prevent similar defects. This study can be used to guide the operation and maintenance of partial discharge in cable terminal.